2020
DOI: 10.1108/ejim-04-2020-0165
|View full text |Cite
|
Sign up to set email alerts
|

Organizational identification perceptions and millennials' creativity: testing the mediating role of work engagement and the moderating role of work values

Abstract: PurposeMillennial-generation employees need to stimulate their creativity to produce innovative ideas, services and products for organizations to flourish and succeed. The main purpose of this research was to discover the mechanism through which organization identification influences employees' creativity in the Chinese organizational context. Particularly, we proposed the mediating role of work engagement and the moderating role of work values in the relationship.Design/methodology/approachA questionnaire sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 70 publications
1
49
0
3
Order By: Relevance
“…Therefore, in today’s dynamic environment, the prime focus of organizations has shifted in identifying various ways of being creative (products and services) as it is essential for them to compete with their rivals (Alzghoul et al , 2018). Past studies have identified organizational identification and work engagement (Hui et al , 2020), social media usage, participative leadership (Chen et al , 2020) and resilience (Anser et al , 2020) as the predictors of EC. McAllister (1995) highlighted the importance of trust in developing unique and valuable ideas (EC).…”
Section: Theorizing and Hypotheses Developmentmentioning
confidence: 99%
“…Therefore, in today’s dynamic environment, the prime focus of organizations has shifted in identifying various ways of being creative (products and services) as it is essential for them to compete with their rivals (Alzghoul et al , 2018). Past studies have identified organizational identification and work engagement (Hui et al , 2020), social media usage, participative leadership (Chen et al , 2020) and resilience (Anser et al , 2020) as the predictors of EC. McAllister (1995) highlighted the importance of trust in developing unique and valuable ideas (EC).…”
Section: Theorizing and Hypotheses Developmentmentioning
confidence: 99%
“…Thus, it is necessary to build a system and culture in which employee engagement can be maintained continuously and it is important to create participation opportunities for various programs to foster learning experiences and relationships among members. Therefore, leaders and HR managers should manage in ways that improve the level of incumbent employee engagement rather than hiring members of the organization who are enthusiastic about their job (Hui, Qun, Nazir, Mengyu, Asadullah and Khadim, 2020). If leaders and HR managers understand the concept of employee engagement accurately through integrated conceptual models, they can more effectively deliberate on which strategies meet the individual needs and well-being of employees to improve efficiency and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Such nested creativity within an organization was also addressed with the notion of person-environment fit (Wang and Wang, 2018 ), suggesting that the congruency between supportive environment for creativity of an organization and creativity of employees improved the process and outcome of NPD. The study of Hui et al ( 2020 ) on the creativity of millennials also demonstrated that the overlapped identities between self and organization led to the creativity of employees agreeing with the innovation orientation of their organization (i.e., novelty and meaningfulness). Creativity was also captured in multiple levels along with the role of team leaders, job characteristics, and organizational identification (Liu et al, 2021 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 95%